2014
DOI: 10.1161/circresaha.115.304262
|View full text |Cite
|
Sign up to set email alerts
|

OxLDL Triggers Retrograde Translocation of Arginase2 in Aortic Endothelial Cells via ROCK and Mitochondrial Processing Peptidase

Abstract: Rationale: Increased arginase activity contributes to endothelial dysfunction by competition for l-arginine substrate and reciprocal regulation of nitric oxide synthase (NOS). The rapid increase in arginase activity in human aortic endothelial cells exposed to oxidized low-density lipoprotein (OxLDL) is consistent with post-translational modification or subcellular trafficking.Objective: To test the hypotheses that OxLDL triggers reverse translocation of mitochondrial arginase 2 (Arg2) to cytosol and Arg2 acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
64
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 48 publications
5
64
0
1
Order By: Relevance
“…29,[101][102][103][104][105] Major causes of l-arginine steal in the blood vessel wall include increased ROS production and activation of Rho-kinase that stimulates both mitochondrial processing peptidase (promoting translocation of arginase from mitochondria to the cytosol and hence increasing its activity) and p38 mitogen-activated PK (phosphorylating transcription factors [activating transcription factor-2 and c-Jun] upregulating the expression and activity of the enzyme); conversely, inhibition of arginases improves endothelium-dependent, NO-mediated dilatations/ relaxations when they are impaired because of upregulation of these enzymes. [100][101][102][103][104][105][106][107][108][109] Another sink for l-arginine can be the induction of iNOS, which is minimally present under physiological conditions, but when expressed/present during infection, chronic inflammation, and in tumors, continuously produces large amounts of NO, thus competing with eNOS for the common substrate and accelerating S-nitrosylation of the enzyme ( Figure 5). …”
Section: Abnormal Coupling Of Endothelial Cell Membrane Receptorsmentioning
confidence: 99%
“…29,[101][102][103][104][105] Major causes of l-arginine steal in the blood vessel wall include increased ROS production and activation of Rho-kinase that stimulates both mitochondrial processing peptidase (promoting translocation of arginase from mitochondria to the cytosol and hence increasing its activity) and p38 mitogen-activated PK (phosphorylating transcription factors [activating transcription factor-2 and c-Jun] upregulating the expression and activity of the enzyme); conversely, inhibition of arginases improves endothelium-dependent, NO-mediated dilatations/ relaxations when they are impaired because of upregulation of these enzymes. [100][101][102][103][104][105][106][107][108][109] Another sink for l-arginine can be the induction of iNOS, which is minimally present under physiological conditions, but when expressed/present during infection, chronic inflammation, and in tumors, continuously produces large amounts of NO, thus competing with eNOS for the common substrate and accelerating S-nitrosylation of the enzyme ( Figure 5). …”
Section: Abnormal Coupling Of Endothelial Cell Membrane Receptorsmentioning
confidence: 99%
“…Although arginase II participates in the endothelial dysfunction, the mechanism through which endothelial NOS activity is regulated remains unclear. However, a novel mechanism showed that oxidized low‐density lipoprotein triggered translocation of arginase II from mitochondria to the cytoplasm via mitochondrial processing peptidase with a simultaneous increase in arginase activity that drove endothelial nitric oxide synthase (eNOS) uncoupling by depleting the substrate pool available for NO biosynthesis 17. Similarily, we also showed that an arginase inhibitor‐enhanced eNOS phosphorylation at Ser117718 and arginase II inhibition improved the loss of mitochondrial membrane potential by a Ca 2+ ‐dependent mechanism and prevented mitochondrial reactive oxygen species (ROS) production 19…”
mentioning
confidence: 99%
“…Arginase 2 Translocation by OxLDL (p 450) 44 Blocking arginase 2 activity reduces severity of atherosclerosis, report Pandey et al…”
Section: Williams and The Editors "In This Issue" Anthology E109mentioning
confidence: 99%